2022
DOI: 10.1108/sampj-07-2021-0288
|View full text |Cite
|
Sign up to set email alerts
|

Embedding and managing blockchain in sustainability reporting: a practical framework

Abstract: Purpose The purpose of this paper is to evaluate blockchain’s enabling role for sustainability reporting. This study extends the scientific knowledge about the impacts related to the notarisation of mandatory sustainability reports through a publicly available blockchain. Design/methodology/approach Building on the idea journey framework, this paper presents the case study of Banca Mediolanum in Italy, a first-mover who notarised its non-financial declaration on a public blockchain to mitigate the informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 72 publications
(121 reference statements)
0
37
0
Order By: Relevance
“…Considering the blockchain effect in organizations and its acceptance, many studies have been done. Pizzi et al (2022) in their study showed the blockchain effect in the submission of sustainability reports. In their study, Ronaghi and Mosakhani (2021), dealt with the effect of accepting blockchain on the social sustainability of enterprises.…”
Section: Introductionmentioning
confidence: 94%
“…Considering the blockchain effect in organizations and its acceptance, many studies have been done. Pizzi et al (2022) in their study showed the blockchain effect in the submission of sustainability reports. In their study, Ronaghi and Mosakhani (2021), dealt with the effect of accepting blockchain on the social sustainability of enterprises.…”
Section: Introductionmentioning
confidence: 94%
“…First, these companies had greater data availability and representativeness within the sector. Regarding the first issue, within the European Union, Directive 2014/95/EU puts the spotlight on large firms by requiring them to present nonfinancial information in relation to social and environmental matters (European Commission, 2014), given the growing interest from stakeholders in knowing about these practices (Pizzi, Caputo, Venturelli, & Caputo, 2022). Second, the implementation of CSR initiatives, such as environmental initiatives, requires large-scale investment, and listed companies have better access to the necessary financial resources (Liao, Luo, & Tang, 2015).…”
Section: Sample Selectionmentioning
confidence: 99%
“…Once more than 2/3 of the users have approved it, this user gets the right to bookmark the new block, i.e. the user can successfully add this startup information to the platform [14]. The platform will automatically execute the corresponding smart contract to package and encrypt this startup information and store it in the new block, which will then be connected to the blockchain [15].…”
Section: Startup Information Platformmentioning
confidence: 99%